Improved rooting capacity and hardening efficiency of carob (Ceratonia siliqua L.) cuttings using arbuscular mycorrhizal fungi - Essahibi, Abdellatif; Benhiba, Laila; Oussouf, Fouad Mohamed; Babram, Mohamed Ait; Ghoulam, Cherki; Qaddoury, Ahmed (Archives of Biological Sciences, 2017)
The present investigation was undertaken to improve the performance of carob cuttings in terms of adventitious roots formation and hardening using arbuscular mycorrhizal fungi (AMF). Softwood cuttings were treated with 5000 mg L-1 of indole-3-butyric acid (IBA) and kept non-inoculated (Non-AM) or inoculated with Funneliformis mosseae (Fmo) alone or combined with Rhizophagus fasciculatus (Fmo+Rfa) or R. intraradices (Fmo+Rin) or both (Fmo+Rfa+Rin) and then maintained under mist conditions. After two months, rooted cuttings were transplanted on sterilized substrate and transferred to a hardening greenhouse for five months. Obtained results showed that inoculation of the rooting substrate with AMF substantially improved the percentage of rooted cuttings and the number of roots per cutting. The highest rooting (63.33%) and number of roots per cutting (11.67) were recorded in the presence of the complex of the three AMF strains (Fmo+Rfa+Rin). Moreover, all mycorrhizal-rooted cuttings survived transplantation and hardening shocks and showed the highest growth and physiological performances. Indeed, in the Fmo-Rfa-Rin-plantlets the gains in plant height and shoot and root dry weights were 95.6%, 55.1% and 76.9% respectively. Furthermore, stomatal conductance, total chlorophyll content, photochemical efficiency of PSII (Fv/Fm) and nutrient concentrations were higher in mycorrhizal plantlets than in non-AM ones. Thus, AMF substantially improved carob cuttings’ performance in terms of rooting capacity and hardening efficiency, thereby increasing the potential of carob propagation by cuttings. https://doi.org/10.2298/ABS160307100E Received: March 7, 2016; Revised: May 2, 2016; Accepted: May 31, 2016; Published online: October 17, 2016 How to cite this article: Essahibi A, Benhiba L, Oussouf FM, Babram MA, Ghoulam C, Qaddoury A. Improved rooting capacity and hardening efficiency of carob (Ceratonia siliqua L.) cuttings using arbuscular mycorrhizal fungi. Arch Biol Sci. 2017;69(2):291-8.